Beyond Media Borders, Volume 2 Intermedial Relations among Multimodal Media - Elleström, Lars (Springer Nature, 2021)
This open access book promotes the idea that all media types are multimodal and that comparing media types, through an intermedial lens, necessarily involves analysing these multimodal traits. The collection includes a series of interconnected articles that illustrate and clarify how the concepts developed in Elleström's influential article The Modalities of Media: A Model for Understanding Intermedial Relations (Palgrave Macmillan, 2010) can be used for methodical investigation and interpretation of media traits and media interrelations. The authors work with a wide range of old and new media types that are traditionally investigated through limited, media-specific concepts. The publication is a significant contribution to interdisciplinary research, advancing the frontiers of conceptual as well as practical understanding of media interrelations. This is the second of two volumes. It contains a concluding article by Elleström and seven contributions concentrated on the issue of media transformations: how media characteristics are transferred and transfigured among various media products and media types.